Awareness and practices of biomedical waste management guidelines 2016 in an upcoming super speciality hospital of east Delhi, India - Bhattar, Sonali; Qureshi, Shariqa; Seth, Rajeev Kumar; Butola, Ruchika; Shingare, Priyanjali (International Journal Of Community Medicine And Public Health, 2018)
Background: Revised and redefined biomedical waste management (BMWM) rules 2016 are an area of immediate focus for the health care personnel amidst the menace created by improper disposal of health care waste, emergence of multi drug resistant superbugs and harmful emissions. Methods: The present cross sectional study was conducted in Rajiv Gandhi Super speciality hospital, Tahirpur, an upcoming referral hospital in east Delhi, India. The study was merged with the training sessions conducted in 13 phases. A self-administered questionnaire pertaining to biomedical waste management rules 2016 knowledge, awareness and practices was used for data collection. Results: Of the 100 respondents consisted of 50 doctors, 30 nurses and 20 technicians, about 54% of HCP were aware about modifications in waste categories. Approximately 42% of the respondents could define sharp waste correctly while 56% had the clarity of changed specifications of BMW bags. Safe injection practices were followed by 47%. Conclusions: Doctors were aware that there had been revision in the biomedical waste management rules in 2016 and its legal aspect but nursing staff was better in the practical implications of the same while the technicians lagged behind in both. It is of prime importance to reinforce comprehensive teaching programmes, spot trainings for the staff and continuous medical education in our hospital setting.